Reflections on the Applicability of the Semiotic Engineering Ontology Extended to the HInt Paradigm - Rodrigues Barbosa, Glívia Angélica; Prates, Raquel Oliveira (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2024: Anais do XXIII Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2024)
Human-Computer Integration (HInt) is a new paradigm that expands the focus of the HCI field to encompass the new relationship of partnership between humans and autonomous technologies. As HInt is an emerging paradigm, the concepts and ontology of Semiotic Engineering Theory have been extended to cover HInt as a special case of HCI. This paper aims to present the results of an evaluation of the applicability and utility of the Semiotic Engineering extension to HInt. In order to conduct the evaluation, an elective undergraduate course on HInt was offered at Federal University of Minas Gerais. The researchers analyzed the material generated by the students' as part of their activities understanding and applying the concepts of the extended Semiotic Engineering theory. The analysis focused on understanding students use and perception of the theory in defining, exploring, and explaining HInt. As contributions, we present insights and reflections on the benefits and limits of the extension of the Semiotic Engineering theoretical framework to support the study, design and evaluation of HInt.